Tool use, or not tool use, that is the question: is the necessity hypothesis really inconsequential for the African great apes? - Masi, Shelly (Frontiers in Mammal Science, 2023)
Investigating drivers of tool use in animals has been recently received great attention because of its implication in understanding animal cognition and the evolution of tool-use in hominins. The Necessity Hypothesis sees tool use as a necessity response to food scarcity, but its role is an ongoing debate. The largest body of literature comparing animal tool-use frequencies comes from primates, particularly from the comparison between the Pan species. This supports the hypothesis that tool use is rarer in wild bonobos because of differential manipulation abilities of chimpanzees rather than different ecological needs. Here, I aim to enrich the discussion concerning the Necessity Hypothesis and the ecological drivers of tool-use in apes. The higher feeding flexibility of bonobos may be a key aspect explaining the lower use of feeding tools when compared to chimpanzees. The diet flexibility of bonobos is similar to that of the lowest level tool users among the wild great apes, the gorilla. Gorillas can thus help to shed further light on this debate. When fruit is scarce, western gorillas and bonobos rely more on widely available proteinaceous herbs than chimpanzees who remain highly frugivorous. Chimpanzees may thus face higher necessity to search for alternatives to obtain high quality food, tool-assisted feeding. An indirect evidence for this higher herbivory is the doubled prevalence of gut ciliates in bonobos than in chimpanzees. In each animal species, a different combination of necessity, opportunities, predisposition and learning processes are likely at play in the emergence of flexible tool use in animals.